Status Consideration and Buying Decisions-A Study with Reference to Kerala - Sumedhan, K. P. (Indian Journal of Marketing, 2011)
Kerala, a small state within Indian Union has become an enigma and a paradox to many economists and development experts at national and international level. Kerala stands much ahead of the other Indian states in terms of social indicators of development, even though the performance of the state in the economic front is dismal. Economic backwardness of Kerala does not reflect in the consumption level of the people. Consumption level of the state is above the national average and many well off states in India. Kerala accounts for more than 12% of the consumer market of the country although it holds less than 4% of the population. Consumption style of the state is characterized by high proportion of expenditure on non-food and non essential item like consumer durables and luxuries similar to those of developed countries. In rural Kerala, expenditure on food and non food items formed 45% and 55% respectively to total consumption expenditure whereas in urban areas, it was 40% and 60% respectively. However, in rural India, food and non-food expenditure constituted 55% and 45% respectively, the same in urban area was 43% and 57%. Kerala is not only better off compared with the national level, but is also standing a great deal more on non food and better off on food items. It reveals that Kerala has been experiencing an unprecedented consumption boom and increase in standard of living. Many economists tried to locate the factors behind such conspicuous consumption in Kerala. Among other factors, literacy, education, rapid urbanization, large scale outmigration of people especially to Middle East, is pointed out as the reasons for peculiar pattern of consumption in the state. The present study is also an endeavour in this regard.